Validity of the Islamic Education Module on Qur'an Hadith Material Based on the Project-Based Learning Model at the Madrasah Tsanawiyah Level - Sri Munawarah; Syafruddin Syafruddin; Fauza Masyhudi (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Validity of the Islamic Education Module on Qur'an and Hadith Material Based on the Project-Based Learning Model at the Madrasah Tsanawiyah LevelObjective: This study aims to develop and test the validity of the Qur’an Hadith learning module based on the Project Based Learning learning model as an innovation in increasing student activeness and understanding of Qur’an and Hadith values in Madrasah Tsanawiyah. Methods: This study used the Research and Development method with the 4D model (Define, Design, Develop, and Disseminate). Data were collected through observation, interviews, and questionnaires. The data analysis used was descriptive. Results: Construct validation on the module has high validity, in the presentation aspect of 91% (valid), the language aspect of 85.7% (valid) and the graphic aspect of 85.7% (valid). Conclusion: The Islamic education module of the Qur'an Hadith meter based on Project Based Learning meets the curriculum standards and the needs of student characteristics and is suitable for use as an alternative teaching material in learning Qur'an Hadith in Islamic education subjects. Contribution: This research contributes as a source of information in developing Islamic education modules based on the Project-Based Learning approach at the Madrasah Tsanawiyah level.INDONESIAN: Validitas Modul Pendidikan Islam Materi Al-Qur’an Hadis Berbasis Model Project Based Learning pada Tingkat Madrasah TsanawiyahTujuan: Penelitian ini bertujuan untuk mengembangkan dan menguji validitas modul pembelajaran Al-Qur’an Hadis berbasis model pembelajaran Project Based Learning sebagai inovasi dalam meningkatkan keaktifan dan pemahaman siswa terhadap nilai-nilai Al-Qur’an dan hadis di Madrasah Tsanawiyah. Metode: Penelitian ini menggunakan metode Research and Development dengan model 4D (Define, Design, Develop, dan Disseminate). Data dikumpulkan melalui observasi, wawancara, dan pengisian angket. Analisis data yang digunakan adalah analisis deskriptif. Hasil: Validasi konstruk pada modul memiliki validitas tinggi, pada aspek penyajian sebesar 91% (valid), aspek bahasa sebesar 85,7% (valid) dan aspek kegrafikan sebesar (85,7% (valid). Kesimpulan: Modul pendidikan Islam meteri Al-Qur’an Hadis berbasis Project Based Learning memenuhi standar kurikulum dan kebutuhan karakteristik siswa dan layak digunakan sebagai bahan ajar alternatif dalam pembelajaran Al-Qur’an Hadis mata pelajaran pendidikan islam. Kontribusi: Penelitian ini berkontribusi sebagai sumber informasi dalam pengembangan modul pendidikan Islam meteri Al-Qur’an Hadis berbasis pendekatan Project-Based Learning pada tingkat Madrasah Tsanawiyah.